2009
DOI: 10.1057/thr.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

Men and Women: Do They Value the Same Things in Mainstream Nightclubs and Bars?

Abstract: This paper explores whether young men and women, the main target market for mainstream nightclubs and bars, have similar or different preference priorities in respect of a first and subsequent visit to these venues. It suggests that an understanding of the gendered nature of place and the differing preferences of men and women can assist businesses in shaping their products and services around the needs of their customers. It suggests that this can be done through a study of preferences and expectations for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In addition, although in part driven by the technologies available, the need for social approval by Gen Y continues to feed the online social networks and Web 2.0 technologies (Bausch & McGiboney, 2009;Richardson, 2009). Alongside the observed trait of online immersion, are those of a need for instant gratification and an overall shortening of attention spans (Fountain & Charters, 2010;Moss, Parfitt, & Skinner, 2009).…”
Section: Generational Theory and Gen Ymentioning
confidence: 99%
“…In addition, although in part driven by the technologies available, the need for social approval by Gen Y continues to feed the online social networks and Web 2.0 technologies (Bausch & McGiboney, 2009;Richardson, 2009). Alongside the observed trait of online immersion, are those of a need for instant gratification and an overall shortening of attention spans (Fountain & Charters, 2010;Moss, Parfitt, & Skinner, 2009).…”
Section: Generational Theory and Gen Ymentioning
confidence: 99%
“…For women entertainment has been shown to be twice as important, in comparison to men, as a motivating factor for them to return to a bar or nightlife experience (Moss, Parfitt, & Skinner, 2009). Barlis-Arizon, Fraj-Andrés, and Matute-Vallejo's (2010) typology of women travelers found that females travel to "live new experiences" (p. 11), pointing toward the escapist element in the experience economy.…”
Section: Mediating Effect Of the 4es On Behavioral Intentionsmentioning
confidence: 99%
“…Kinghorn and Willis () found that providing worthwhile participatory activities, extending opening hours and featuring locally relevant displays, created more incentives and opportunities for people to visit with friends and family while also enhancing both bridging and bonding social capital amongst those visitors in the process. The tendency of Gen Y to be hedonistic and to live for the moment, however, does mean that they are constantly on the lookout for ‘the next big thing’ (Nancarrow et al ., ; Moss et al ., ).…”
Section: Generation Y and Consumption Experiences: Lessons For Visitomentioning
confidence: 99%
“…Kinghorn and Willis (2008) found that providing worthwhile participatory activities, extending opening hours and featuring locally relevant displays, created more incentives and opportunities for people to visit with friends and family while also enhancing both bridging and bonding social capital amongst those visitors in the process. The tendency of Gen Y to be hedonistic and to live for the moment, however, does mean that they are constantly on the lookout for 'the next big thing' (Nancarrow et al, 2002;Moss et al, 2009). Jennings et al (2010) feel that the interconnectivity of the entire visit experience, right through from pre-visit to post-visit, is highly important to Gen Y who are frequently more than willing to pay relatively high prices if they can be assured that they will have the truly memorable experiences they seek.…”
Section: Consumer Experiencesmentioning
confidence: 99%